Relationship Between Knowledge and Application of APAR as a Fire Fighting Effort - Ghaffari Dhani Kurniawan (Media Karya Kesehatan, 2023)
APAR is a light tool that can be easily operated by one person to extinguish a fire when it starts. Based on data from the Central Java Karanganyar Province Central Statistics Agency, there were no fire cases in 2021. Based on the results of a preliminary study of respondents, there were cases of APAR canisters exploding. The aim of this research is to analyze the influence of the relationship between knowledge and the application of APAR. This research uses a quantitative research method with a cross sectional approach. The total population in this study was 120 people. The research sample consisted of 92 respondents. The sampling technique uses simple random sampling. The data analysis technique uses the Chi-Square statistical test. The results of this research show that the majority of workers have a good level of knowledge and have appropriate applications as many as 40 people (43.5%), while knowledge is not good and have inappropriate applications as many as 17 people (18.5%). The results of the chi square statistical test analysis obtained p = 0.047 (p < 0.05), so there is a relationship between knowledge and the application of APAR in the production department. These results are supported by the RP value (95% CI) = 1.002 < 6.05. From the results above, it can be concluded that respondents who have appropriate APAR implementation are in the good knowledge category. This is reinforced by the respondents' knowledge increasing through socialization or training that can be applied while in the field. Conclusion: There is a relationship between knowledge and the application of APAR at PT. X. Suggestions for PT. X is expected to provide outreach and training on active fire protection. Keywords: APAR, fire, knowledge.